A novel SARS-CoV-2 related coronavirus in bats from Cambodia - Deborah Delaune (Nature Portfolio, 2021)
In this study, Delaune et al., isolate and characterise a SARS-CoV-2-related coronavirus from two bats sampled in Cambodia. Their findings suggest that the geographic distribution of SARS-CoV-2-related viruses is wider than previously reported.